Black Lycium barbarum polysaccharide attenuates LPS-induced intestine damage via regulation gut microbiota - Yan, An; Ding, Houkang; Liu, Junjun; Bi, Chongliang; Han, Zhaoqing; Wang, Zhennan; Nawaz, Shah; Shen, Yizhao; Liu, Shudong (Frontiers in Microbiology, 2023)
Lycium barbarums are traditionally used as a homology of medicinal plants in China with a potent role in metabolism and immunomodulation. The current study was performed to explore the attenuation effect and microbiota regulation of Lycium barbarum polysaccharide (BLBP) on lipopolysaccharide (LPS)-induced intestine damage in mice. A total of 70 mice were randomly divided into five groups; negative control (GA), LPS (GB), both treated with an equal volume of normal saline, and BLBP treatment groups GC (100 mg/kg), GD (200 mg/kg), and GE (400 mg/kg) via gavage for 19 days. On Day 19, mice in groups GB, GC, GD, and GE were treated with 10 mg/kg LPS for 24 h and euthanized to collect intestine samples for pathological examination and microbiota sequencing. The results showed a non-significant difference in body weight gain among the five mouse groups; however, mice in the GC and GE groups showed decreased weight gain. An H&E examination revealed that the integrity of intestinal villi was destroyed by LPS, while BLBP supplement alleviated intestinal damage with an increase in villus height and a decrease in crypt depth. A total of over 59,000, 40,000, 50,000, 45,000, and 55,000 raw sequences were found in groups GA, GB, GC, GD, and GE, respectively. LPS challenge decreased alpha diversity indexes significantly (p < 0.05), while a non-significant difference was found between different BLBP treatment groups and the GA group. A total of 8 phyla and 13 genera were found among five mouse groups, and BLBP partly restored the bacterial abundance in mice. LPS changed 282 metabolic pathways in KEGG L2, 77 metabolic pathways in KEGG L3, and 205 metabolic pathways in MetaCyc, respectively. The BLBP-supplemented groups, especially GE, showed reverse effects on those metabolic pathways. The current study revealed that BLBP can effectively decrease intestinal damage through the regulation of intestinal microbiota, which may provide new insights for the prevention of intestinal disease using food and medicine homologous of Lycium ruthenicum.